2021
DOI: 10.1002/ijgo.13850
|View full text |Cite
|
Sign up to set email alerts
|

Improving systems of prenatal and postpartum care for hyperglycemia in pregnancy: A process evaluation

Abstract: Objective To identify successes to date and opportunities for improvement in the implementation of a complex health systems intervention aiming to improve prenatal and postpartum care and health outcomes for women with hyperglycemia in pregnancy in regional and remote Australia. Methods A qualitative evaluation, underpinned by the RE‐AIM framework (reach, effectiveness, adoption, implementation, maintenance), was conducted mid‐intervention. Semi‐structured interviews were conducted with the participants, who i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“… 17 The investigators also reported lower overall uptake of any postpartum screening by 6 months than our study (including OGTT, HbA 1C , fasting or random plasma glucose). In contrast to that study, the improved uptake reported in our cohort may reflect increased awareness in recent years of the importance of postpartum screening, 21 as well as changes to government reimbursement for HbA 1C testing. As expected, given the relative ease of the test, when an HbA 1C is included in postpartum screening, rates markedly improve.…”
Section: Discussioncontrasting
confidence: 87%
“… 17 The investigators also reported lower overall uptake of any postpartum screening by 6 months than our study (including OGTT, HbA 1C , fasting or random plasma glucose). In contrast to that study, the improved uptake reported in our cohort may reflect increased awareness in recent years of the importance of postpartum screening, 21 as well as changes to government reimbursement for HbA 1C testing. As expected, given the relative ease of the test, when an HbA 1C is included in postpartum screening, rates markedly improve.…”
Section: Discussioncontrasting
confidence: 87%
“…This differs considerably to studies investigating continuous glucose monitoring for women with type 1 diabetes in pregnancy, where all patients commenced in the first trimester and >70% had sensor activity >75%. 4 Improving referral pathways, 6 culturally appropriate health systems, 3,6 and ensuring access to diabetes educator time and expertise are essential to support optimal use of this technology.…”
mentioning
confidence: 99%
“…This special issue brings together strengths-based research which presents voices and actions that can be heard and taken forward in order to make a difference. The issue highlights the voices of those usually not heard in research, in clinical care, and in health service design, [1][2][3][4][5][6] and calls out the silence and invisibility commonly imposed on Indigenous women. [7][8][9][10][11] This Special Issue includes calls from Indigenous researchers through Indigenous-led and -conducted research; and calls from Indigenous women, either through telling the stories of their health and healthcare journeys, 1,12,13,14 or through risk factors and health outcomes being made visible in quantitative data, 8,15,16 or through looking at existing literature in new ways.…”
mentioning
confidence: 99%
“…The articles in this special edition use positive approaches. This is done in order to empower women in healthcare, 12 to develop and trial culturally safe and community-based approaches, 2,6 to partner with communities, 3,5 to employ Indigenous methods and knowledge, 8,14 to privilege Indigenous voices, 4,9,10,11 to move towards risk assessment and management tailored to Indigenous populations and context, 15,16 and to explore women's experiences in new ways. 1,9,13 Much of the research responds to the silence/invisibility of First Nations and Indigenous women by challenging the norms of women's healthcare provision, such as persistent discrepancies in structural/social determinants of health, healthcare access and health outcomes, systemic racism, and trauma.…”
mentioning
confidence: 99%
See 1 more Smart Citation